Driving forces for research and development strategies: An empirical analysis based on firm-level panel data - Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2007)
This paper investigates empirically different ways to organize R&D within Swiss firms. Based on a longitudinal data set comprising three cross-sections (1999, 2002, and 2005) of the Swiss innovation survey, four different types of R&D strategies were identified: firms combine in-house R&D with R&D co-operations (coop), or in-house R&D with external R&D (buy), or they conduct in-house R&D, external R&D and R&D co-operations (mixed), or they exclusively rely on in-house R&D (make). It is the aim of this paper to understand what drives firms to apply different strategies. Based on econometric estimations controlling for correlations between the dependent variables and endogeneity among the independent variables it was found that concepts related to the absorptive capacity, incoming spillovers and appropriability, the importance of different knowledge resources, the competitive environment, costs and skill aspects as well as technological uncertainty are essential factors that determine a firm's decision to choose a specific way to organize R&D.
Keywords: O30; 330; Research and Development; R&D Co-operations; Empirical Analysis (Firm Panel); R&D Strategies; Industrielle Forschung; Unternehmenskooperation; Unternehmensorganisation; Schweiz